Analisis Capaian Pembelajaran Elemen Jati Diri Pada Peserta Didik PAUD di Kecamatan Jenawi Kabupaten Karanganyar - Hidayah, Anisa Nur; Ali Formen; Diana (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Many pre-school children still experience psychosocial problems, especially social-emotional problems such as aggressive behavior or anxiety. which results in negative development and readiness to enter the next level of school. The purpose of the study was to determine the profile of the elements of learning outcomes of learners' identity in Jenawi District Kindergarten and to find out the teacher's approach in the elements of learning outcomes of learners' identity in the independent curriculum in Jenawi District Kindergarten. The research used is a type of quantitative descriptive research in this study aims to determine the learning outcomes of the elements of early childhood identity in Jenawi District. Respondents in quantitative research are children aged 4-6 years. The sample in this study is a total of 221 children who attend kindergarten institutions spread across Jenawi, Karanganyar. Data collection techniques using questionnaires, namely with favorable and unfavorable questions using a Likert scale. Descriptive percentage analysis is used. Data management is processed using Microsoft excel with the help of several formulas in Microsoft excel. The results of the final descriptive data analysis, the results of the calculation of the learning achievements of the elements of identity in PAUD students represented with a minimum value of 47 and a maximum value of 80. while the average is 65.51 with a standard deviation of 8.01.